Pengembangan Layanan Bimbingan Kelompok Berbantu Media Board Game PathFinder Untuk Meningkatkan Motivasi Belajar Siswa Kelas VIII SMP Negeri 1 Kabat - Wazirotus Sakinah; Ratna Wulandari; Fajar Wahyu Prasetyo (MAN Insan Cendekia Jambi, 2026)
The absence of a group guidance service product assisted by Board Game PathFinder media to improve the learning motivation of eighth-grade students at SMP Negeri 1 Kabat constitutes the main problem underlying this study. This research aims to develop group guidance services assisted by Board Game PathFinder media that are feasible, practical, and effective in improving students' learning motivation. The method used was Research and Development (R&D) 4-D development model (Define, Design, Develop, Disseminate). The research subjects included two content experts, two media experts, two practitioners/guidance and counseling teachers, and five eighth-grade students as limited trial subjects. Data collection instruments consisted of expert validation questionnaires, student response questionnaires, and learning motivation questionnaires (pretest-posttest). Data analysis techniques used percentage analysis of feasibility and Paired Sample t-test. The results showed that: (1) content expert validation obtained feasibility percentages of 84,66% for the Board Game PathFinder media and 87.50% for the guidebook, categorized as highly feasible; (2) media expert validation obtained percentages of 96,43% for the media and 95.83% for the guidebook, categorized as highly feasible; (3) practitioner assessment obtained percentages of 98.33% for the media and 97,50% for the guidebook, categorized as highly feasible; (4) student responses were 79.47% for the media (good category) and 83.50% for the guidebook (very good category); and (5) the effectiveness test showed an increase in average learning motivation from 66.8 (pretest) to 80.8 (posttest) with Paired Sample t-test results of Sig. (2-tailed) = 0.002 < 0.05, indicating a significant difference. Therefore, group guidance services assisted by Board Game PathFinder media are declared feasible, practical, and effective in improving the learning motivation of eighth-grade students at SMP Negeri 1 Kabat.